Short Videos & Social Media Algorithms: Effective Communication in Tourism Marketing - Dewi Yanti; Agus Dedi Subagja; Siti Nurhayati; Syailendra Reza Irwansyah Rezeki; Christine Herawati Limbong; Rahmad Solling Hamid (International Journal of Artificial Intelligence Research, 2022)
More and more users and business owners are gravitating toward short films. Short videos are now more engaging and entertaining due to more interactive engagements and the development of artificial intelligence technology like facial recognition. Short video marketing communications emerged due to the rapid growth of short videos. Social media usage is one kind of short video marketing communication. Short videos can now be uploaded to social media platforms for communication. TikTok is one of those social media sites. To sell its app, TikTok uses short movies that, thanks to an algorithm, quickly become viral hits. This study aims to identify Social Media Algorithms and Short Videos as Effective Communication Media in Tourism Marketing. Descriptive techniques are used in this study's qualitative methodology. The findings of the study demonstrate how social platforms like TikTok, which use algorithms based on user preferences and short films uploaded to social media, have changed how prospective tourists learn about places to visit the use of brief videos through social media platforms as marketing communications influences tourists' perceptions of destination image and tourist intentions, with interactive marketing playing a more significant role. This study investigates empirically the influence of usage on perceptions of destination image and tourism intentions. Regarding the effect of visitor intention, the influence of tourist attractions and accommodations is greater than that of short video marketing on image perception.